Youth Political and Social Media Engagement for 2024 Indonesian General Elections - Ayu Candraningrum, Diah; Gafar Yoedtadi, Muhammad; Djunaidi, Ahmad; Setyanto, Yugih; Savitri Setyo Utami, Lusia; Retno Hapsari, Zita; Utami, Budi (School of Communication Science and Media Business, 2025)
Indonesia has entered a new chapter of politics under the leadership of President Prabowo Subianto and Vice President Gibran Rakabuming Raka. The pair won unanimously in the 2024 General Election, with 58.6% of the vote, the majority of which went to young voters. Indeed, in the 2024 elections, the number of young voters aged 22-30 years was the largest group of voters. A total of 114 million voters, who are millennials and Generation Z, have proven to be able to change political policies in this country for the next 5 years. Half of these young voters are first-time voters. Before the democratic party was held, there were many doubts about the existence of these young people considering the character of Gen Z and millennials is known as an adaptive and responsive generation that will affect their attitudes and behavior. They are also known to be disinterested in political issues, but this is expected to change based on the social media content they see. As a result, issues of polarization, misinformation, and disinformation on social media loomed during the election period. This research uses the concepts of youth politics and social media engagement to achieve the goal of knowing how these young voters use social media to find information related to honest and anti- corruption leadership candidates. This research also uses a qualitative approach with a phenomenology research method and data collection as qualitative and quantitative data. The qualitative data was collected from interviews with 2 Generation Z, while quantitative data was collected sourced from distributing an online survey to 114 Generation Z regarding the use of social media for political campaigns. This refers as amplifier data. The results of the study stated that young voters are very dependent on algorithms running on social media accounts to get information about candidates to be elected in the General Election. In addition, they are also helped by the presence of For Your Page (FYP) on social media, although the content they prefer is classified as misinformation and disinformation.